Effect of Heating Treatments on Nutritional and Antinutritional Contents of Flaxseed Flour (Linum usitatissimum) as Poultry Feed - Churriyah, Rosyidatul; Sjofjan, Osfar; Natsir, Muhammad Halim (Universitas Halu Oleo, 2022)
ABSTRACT This research aimed to evaluate the effect of several heating treatments on the nutritional and antinutritional content of flaxseed flour as a poultry feed. Raw brown flaxseed was picked as the material. The method of this research was a laboratory analysis using a completely randomized design (CRD) with 5 treatments (T0: without heating as a control, T1: sand fried flaxseed, T2: steamed flaxseed, T3: autoclaved flaxseed, T4: microwaved flaxseed) and 5 replications. The variables observed were dry matter, crude protein, crude fat, crude fiber, ash, gross energy, tannin, and phytic acid. The data were analyzed by analysis of variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT). The result showed that several heating treatments had a highly significant effect (p<0.01) on all of the variables observed. Heating treatments given to the flaxseed flour showed a general reduction trend to the nutritional and antinutritional content at different rates, but the losses in antinutritional content of microwaved flaxseed flour were higher than the other treatments. It concluded that microwaved flaxseed gives the best results to be used as poultry feed.Keywords: antinutrient factor, flaxseed, heat treatment, nutrient value